Relationship between the endopelvic fasciae and the inferior hypogastric plexus Activity Log (International Journal of Medical and Surgical Sciences, 2020)
The Inferior Hypogastric Plexus (PHI) is a difficult plexus to define and dissect, hence the ease with which it can be injured both in anatomical and surgical research. Defining its relationships, with respect to the endopelvic fascia (FEP), including its formation and  branches, (Baader B., et al., 2003, p. 129) would facilitate their dissection. This anatomical investigation aims to standardize different portions that require a different approach to preserve their integrity.Cadaveric material belonging to the Third Chair of Anatomy of the School of Medicine, Buenos Aires University was used. One (n=1) formolized male adult organ block and seventeen (n=17) hemipelvis were dissected: five (n=5) adult male hemipelvis formolized, nine (n=9) fetal hemipelvis formolized (7 male and 2 female), between 18 and 36 weeks of gestational age calculated by femoral length, and three (n=3) adult hemipelvis from fresh cadavers, two (n=2) female and one (n=1) male. Microdissection elements and magnifying glasses were used.We were able to distinguish three different sectors: the first, preplexual, located posterior and lateral to the FEP, where the sympathetic components (hypogastric nerves) and the parasympathetic (pelvic splanchnic nerves) have not yet converged to form the plexus. A second sector, plexual, with the plexus already fully formed, located in the thickness of the FEP. Finally, its terminal portion, already devoid of the FEP, formed by nerves that go to the perineal membrane accompanied by arterial and venous vessels. Each of these sectors requires a different approach in both anatomical and surgical dissection.
Keywords: pelvic fasciae, inferior hypogastric plexus, pelvic spaces